Archives Management in Support Official Administration in Toho Subdistrict Head Office, Mempawah Regency - Martinus Martinus; Nahot Tua Parlindungan Sihaloho; Dina Nur Shadrina (Yayasan Ilomata, 2022)
This study aims to analyze and describe the management of archives in support of administrative order at the Toho sub-district office, Toho district, Mempawah regency. This problem was chosen to look at the issues that exist in the management of archives or archives that exist, especially in the Toho District office of Mempawah Regency, especially those related to the problem of managing letters and arranging archives at the Toho Sub-district office because there are phenomena that indicate where in the management, mail or control. And the arrangement of the archives is still not done well; in other words, it has not been done as desired, or there are still some obstacles, especially those related to archive problems. Therefore, the archive is essential in supporting the orderly administration in the office so that there are no archiving problems that will make the paperwork in the office not recorded neatly or adequately. The results of this study indicate that the management, control, and arrangement of archives or archives at the Toho sub-district office are still not carried out properly, so an understanding of adequate archival equipment procedures is needed so that activities in archives management can be carried out as well as possible. This must be guided by the Governor's Regulation No. 453 of 2005 concerning reasonable and correct archival procedures.